The effects of workload difference between limbs in plyometric and strength exercises in reducing asymmetry in change of direction ability during basketball season - Ujakovic, F.; Sarabon, N. (The Journal of Strength and Conditioning Research, 2023)
The topic of interlimb asymmetries has recently been extensively investigated; despite that, intervention for purpose of reducing them have been narrowly examined. The present study investigated the effects of maximal strength and plyometric resistance training program with 3:1 workload ratio (nondominant to dominant side) on change of direction deficit (CoDdef) asymmetry during the basketball season. Thirty-six highly trained male basketball players (19.3 ± 4.9 years) from different age categories (U-17, U-19, and senior) were divided into 2 groups: the control group (n = 18) and the intervention group (n = 18). The intervention group performed once-a-week training that consisted of strength (Bulgarian split squats) and jumping (single-leg countermovement jumps [SLCMJs]) part in which nondominant-to-dominant workload ratio was 3:1 during the 8-week period. Preintervention and postintervention testing included single-leg isometric squat, SLCMJ, 10-m sprint, and 505 test. Analysis of covariance results showed a statistically significant difference with large effect size (p < 0.05; ?2 = 0.26) when preintervention asymmetry was included as covariate. Post hoc analysis showed a statistically significant decrease in mean CoDdef asymmetry between preintervention (11.88%) and postintervention (4.47%) testing (p < 0.01, effect size [ES] = -1.37). Isometric squat strength increased on nondominant side in the intervention group (p < 0.05; ES = 0.77). No other performance or asymmetry variable showed significant change. In conclusion, a 3:1 workload of nonspecific movement task in favor of nondominant limb is an effective training strategy to reduce CoDdef asymmetry during basketball season.